PENGARUH E-SERVICE QUALITY DAN E-TRUST TERHADAP KEPUASAN NASABAH PENGGUNA WONDR BY BNI MELALUI CITRA BANK SEBAGAI VARIABEL INTERVENING - Regita G. Rondonuwu; Silvya L. Mandey; Arrazi Hasan Jan (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
This study aims to examine the influence of e-service quality and e-trust on customer satisfaction, as well as their impact on bank image, and the effect of bank image on customer satisfaction among users of the Wondr by BNI. The research adopts a quantitative approach using a survey method by distributing questionnaires to 100 respondents who are customers of Wondr by BNI. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique through the SmartPLS software. The findings reveal that the independent variables analyzed, namely e-service quality and e-trust, have a positive and significant direct effect on both customer satisfaction and bank image. Furthermore, bank image also shows a positive and significant direct influence on customer satisfaction. These results indicate that the effectiveness of electronic service quality and the level of customer trust in the Wondr by BNI application significantly contribute to building a favorable bank image and improving customer satisfaction. This research is expected to provide academic contributions to the development of digital service marketing studies and offer practical recommendations for Bank BNI in enhancing service quality and strengthening customer trust through improvements in digital banking features and security.